A Digest of the Laws of Pennsylvania, from the Year One Thousand Seven Hundred to the Tenth Day of July, One Thousand Eight Hundred and Seventy-Two, at 1051, Militia, pt. 10, § 102 (10th ed., vol. 2, 1873) - (:unkn) unknown (My University, 1864)
A soldier who unnecessarily, or without order from a superior officer, comes to any parade with his musket, rifle or pistol loaded with ball, slug or shot, or so loads the same while on parade, or unnecessarily or without order from a superior officer, discharges the same, when going to, returning from, or upon parade, shall forfeit not more than twenty dollars, to the use of the brigade fund.
Keywords: ARMED FORCES